Accuracy of computer-assisted iliosacral screw placement using a hybrid operating room. Issue 2 (February 2016) - Richter, P.H.; Gebhard, F.; Dehner, C.; Scola, A.
Abstract: Introduction: In recent years hybrid operating rooms were established all over the world. In our setting we combined a 3D flat-panel c-arm (Artis zeego, Siemens) with a navigation system (BrainLab curve, BrainLab). This worldwide unique combination enables the surgeon to visualise an entire pelvis in CT-like image quality with a single 3D-scan. The aim of our study was to investigate, if utilisation of a hybrid operating room increases the accuracy of SI-screws in comparison to standard 3D-navigation. Material and methods: Retrospective, not randomised single centre case series at a level I trauma centre. Inclusion criterion was insertion of a percutaneous iliosacral screw using image-guidance in the hybrid operating room. 61 patients (35 female, 26 male) were included from June 2012 till October 2014. 65 iliosacral screws were inserted. Intraoperative 3D-scans and postoperative scans were examined to investigate screw placement. The results were compared to a preceding study performed in 2012 using conventional 3D-navigation. Statistical calculations were performed with Microsoft Excel 2011 and SPSS. Results: 65 iliosacral screws were implanted. Two different types of screws were implanted: 1. "Standard" iliosacral screws stabilizing one joint/a unilateral fracture. 2. Single SI-screws stabilizing both SI-joints and if present a bilateral fracture. Forty one patients were included in group 1 (screws n = 45). There was no perforation in 43 screws, grade 1 perforation in 2 screws. There was no grade 2 or 3 perforation in this group. Compared to the conventional 3D-navigated screws there was a highly significant difference ( p < 0.001). Twenty patients could be included in group 2. Eleven screws showed a complete intraosseous position. There was grade 1 perforation in 2 screws, grade 2 perforation in 5 screws and grade 3 perforation in 2 screws. Conclusion: Improvements in image quality and enlargement of the display window lead to better intraoperative visualisation of the entire dorsal pelvis. Thereby the accuracy of computer-assisted iliosacral screws could be increased using a hybrid operating room. Furthermore difficult tasks like a single screw for both joints can be accomplished.